12-mJ 1-kHz cryogenically cooled rod Yb:YAG regenerative amplifier - Zhang, Guangyin; Li, Ruixuan; Li, Kui; Li, Jie; Bai, Zhenao; Fan, Zhongwei (Frontiers in Physics, 2024)
We report on a continuous-wave (CW) pumped cryogenically cooled rod Yb:YAG regenerative amplifier delivering uncompressed 12-mJ, 90-ps, 1030-nm pulses at a 1-kHz repetition rate. The amplifier demonstrates an efficiency of 31.7%. A symmetric cavity design was utilized to compensate for the substantial thermal lensing effect, yielding a final measured beam quality of 1.1 in both horizontal and vertical directions. After significant gain narrowing, the measured spectra exhibit a bandwidth of 0.3 nm corresponding to an approximately 5 ps transform-limited pulse.